Preliminary conceptual design and thermodynamic comparative study on vapor absorption refrigeration cycles integrated with a supercritical CO2 power cycle. (1st April 2018) - Li, Hang; Su, Wei; Cao, Liyan; Chang, Feng; Xia, Wenkai; Dai, Yiping
Highlights: A novel combined cooling and power system is proposed. A comparative study is conducted between two combined cycles. Quantitative parametric analysis is carried out. Intelligence algorithm optimization is adopted to the system. Abstract: Combined cooling and power system has gained extensive attention from government and publics throughout the world due to fuel saving, high energy utilization efficiency and different energy forms output. In this paper, a novel combined cooling and power system comprising a supercritical CO2 (sCO2 ) power cycle and a vapor absorption refrigeration cycle with lithium bromide as the working fluid is proposed. A comparative study is conducted between this system and the combined sCO2 /ammonia-water system to show its advantages and potential on the basis of the self-built thermodynamic simulation platform. The influence of different variables including turbine inlet temperature, pressure ratio in sCO2 cycle and evaporating temperature on the system performance is analyzed. Single-objective optimization relying on the genetic algorithm and multi-objective optimization based on the NSGA-II method are used to further investigate and compare the performance of above two cycles. Optimization results reveal that compared with the combined sCO2 /ammonia-water system, the proposed sCO2 /LiBr-H2 O system could gain improvement on CORP by 0.3112 at the expensive of COPP drop by 0.0004 excepting the advantage of extreme low pump outlet pressure in bottoming cycle. Besides, sCO2 /LiBr-H2 O system is relatively easier to reach the balance between power and cooling.